From De Facto Fact-finder to Expert Witness? Transition of Forensic Examination in China - Thomas Y Man (Wolters Kluwer Medknow Publications, 2015)
Forensic examination plays an important role in China's judicial system, especially in the fact-finding process of both civil and criminal proceedings. Since 2005, this system has experienced gradual, yet significant changes. This paper seeks to examine the major themes of these changes in the context of the continued conceptual reformulation and structural realignment of civil and criminal procedures and the ongoing effort to codify evidence law with transforming impact on China's judicial system and culture. Emphasis is given to the transition of the forensic examination system from an officially (both administrative and judicial) administered fact-finding mechanism with powerful impact on the courts' truth-seeking activities to, at least partially, an expert witness system with significant participation and control by the parties' to judicial proceedings. A convergence of influence from both the continental inquisitorial tradition and the common law adversarial structure appears to have strongly informed the process and direction of the Chinese forensic examination reform. This paper attempts to explain the reasons for this convergence of influence, identify the trend and direction of this development, and provide observations and suggestions for further improvement of the forensic examination system in several key aspects with particular reference to the legal principles and judicial practices under the Federal Rules of Evidence of the United States.